Business Cycle Dynamics in the Euro Area: A Factor-SVAR Approach - Atilim Seymen (FIW - Research Centre International Economics, 2009)
The study investigates the business cycle dynamics in the euro area using an empirical framework which comprises common global and euro area shocks as well as allows bilateral spillovers of country-specific shocks across the member economies. Three core questions lie at the heart of the analysis: (i) To what extent are the business cycles of the euro area countries driven by common and spillover shocks? (ii) What are the extent and sources of business cycle heterogeneity in the euro area? (iii) Which mechanisms led to the moderation of business cycle activity in the euroarea until recently?
Keywords: E32; C32; F00; O52; 330; Euro Area Business Cycles; Common and Country-Specific Shocks; Spillovers; Factor-Structural Vector Autoregression